An investigation into religious instruction in state high schools in the Cape Province - Penny, Alan Joseph (Rhodes University, Faculty of Education, Department of Education, 1971)
From Preface: The question of religious instruction in Cape Schools first aroused my interest when I was subjected to anything but religious tnstruction during my own high school years. My desire to enquire into the whole position of religious instruction in the high school curriculum grew out of an essay on the role of religion in the education of the child which I wrote whilst reading for the B.Ed. degree. As background, I read Harold Loukes' classic Teenage Religion, and from then onwards, I felt that it was necessary to undertake an investigation of this kind in the Cape Province. My aim was not only prompted out of a desire to expose what I already knew to be an educationally and religiously unsound and unhealthy state of affairs, but more deeply because I, although an ignorant amateur in theology, am aware that too often the traditional religious foundations, poorly built by unintelligent teaching, are shaken, if not destroyed, by scientific discovery and material advancement.
Keywords: Religious education -- South Africa -- Cape of Good Hope; Religious education of teenagers